2016
DOI: 10.1016/j.jsxm.2016.05.011
|View full text |Cite|
|
Sign up to set email alerts
|

A Phase 3 Study to Evaluate the 1-Year Efficacy and Safety of Udenafil 75 mg Once Daily in Patients with Erectile Dysfunction

Abstract: Introduction Once-daily administration of phosphodiesterase type 5 inhibitors has been shown to correct erectile dysfunction (ED). Aim To evaluate the long-term efficacy and safety after once-daily oral administration of udenafil 75 mg in men with ED. Methods This clinical trial was an open-label, fixed-dose, 24-week extension study (DA8159_EDDL_III) of a 24-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…PDE5 inhibitors are widely prescribed for the treatment of patients with ED. PDE5 inhibition prevents the degradation of cyclic guanosine monophosphate and elevates NO bioavailability [78]. In addition, numerous studies have reported that PDE5 inhibitors have beneficial systemic effects.…”
Section: Combined Treatment With Metformin and Phosphodiesterase 5 Inmentioning
confidence: 99%
See 1 more Smart Citation
“…PDE5 inhibitors are widely prescribed for the treatment of patients with ED. PDE5 inhibition prevents the degradation of cyclic guanosine monophosphate and elevates NO bioavailability [78]. In addition, numerous studies have reported that PDE5 inhibitors have beneficial systemic effects.…”
Section: Combined Treatment With Metformin and Phosphodiesterase 5 Inmentioning
confidence: 99%
“…It has been established that obesity and ED share an internal pathological environment, thus, targeting obesity as an underlying factor of ED may be an important therapeutic approach to maximize the efficacy of treatment. Moreover, once daily prescription for a long time with low dose PDE5 inhibitors is settled down as a trend of ED treatment currently [78]. It has become increasingly important to focus on the systemic and metabolic effects of PDE5 inhibitors, especially in patients with ED and comorbid medical conditions.…”
Section: Combined Treatment With Metformin and Phosphodiesterase 5 Inmentioning
confidence: 99%